ANTI HISTAMINIC, ANTI CHOLINERGIC AND SEDATIVE ACTIVITIES OF FEXOFENADINE ANALOGUE - SATHISH NAGARANAVILE K,; SENTHIL KUMAR GP, (International Journal of Pharma and Bio Sciences, 2010)
The Fexofenadine analogue 4-(4-(4-(Hydroxy diphenyl methyl)-1-piperidinyl)-1-oxo butyl)-fluorobenzene (analogue I) was screened for anti-histaminic activity by guinea pig tracheal chain, anticholinergic by guinea pig tracheal chain and sedative activity. The antihistamine effect of analogue I was examined by producing cumulative log concentration response curve of histamine acid phosphate induced contraction of tracheal chains 10 minutes after exposing tissue to compound at different dose levels (20 μM, 60 μM, and 200 μM), and histamine 0.001 μM. The effect of different concentrations of Analogue I was tested on each trachea, the concentration response curve to acetylcholine was constructed by cumulative addition of acetylcholine in absence and in presence of antagonists. Analogue I was incubated with the tracheal chain preparation for 30 minutes before addition of cumulative concentration of acetylcholine. Spontaneous motor activity was performed using Actophotometer. Results of the treated groups were compared with those of control group at each time interval. SMA measurements started 30 minutes after the administration of the compound and the results were compared with those of control. analogue I exhibited significant anti-histaminic activity, anticholinergic activity and less sedative effect against various models.